Plasmonic Seasoning: Plasmonic Seasoning: Giving Color to Desktop Laser 3D Printed Polymers by Highly Dispersed Nanoparticles (Advanced Optical Materials 15/2020). Issue 15 (5th August 2020) - Hupfeld, Tim; Wegner, Andreas; Blanke, Meik; Doñate‐Buendía, Carlos; Sharov, Vladyslav; Nieskens, Simon; Piechotta, Markus; Giese, Michael; Barcikowski, Stephan; Gökce, Bilal
Abstract : Bilal Gökce, Stephan Barcikowski and co‐workers (article number 2000473 ) establish a colloidal additivation process to decorate commercial thermoplastic polyurethane polymer micropowders with laser‐synthesized silver nanoparticles at the kg scale. The nanoparticles act as photothermal, plasmonic sensitizers already at ppm concentration level and enable laser 3D printing with a diode laser. This work demonstrates that the synthesis of new feedstock materials could facilitate the ability of the 3D printing method of laser powder bed fusion to penetrate the market of desktop 3D printers.